Pteris pseudoamoena (Pteridaceae), a new species from Guangxi, China and Vietnam - Guo, Rui; Wang, Jia-Mei; Zhang, Wen; He, Dan; Yu, Jing; Yang, Dong-Mei (Phytotaxa, 2022)
A new species of fern, Pteris pseudoamoena (Pteridaceae), was identified and characterized. It is currently found in Guangxi Province, China, and Vietnam. Pteris pseudoamoena shares similar morphological characters with P. amoena and P. mcclurei, but can be distinguished by spores with echinate-tuberculate and auriculate ornamentation, straw-colored stipes, rachises and costae, and mostly free, occasionally interlinked veins. In addition, molecular evidence indicated that the new species is sister to a clade consisting of P. amoena, P. nakasimae and P. mcclurei.